Does spirituality correlate with students’ empathy during covid-19 pandemic? the case study of Indonesian students - Fitriyah, Fifi Khoirul; Saputra, Nopriadi; Dellarosa, Maretha; Afridah, Wiwik (COUNS-EDU: The International Journal of Counseling and Education, 2020)
Covid-19 pandemic has affected all parts of human life. It affects health, as well as socio and economic aspects. In this situation, high empathy should follow the implementation of physical distancing to reduce the spread of the virus. However, anti-social behavior has mostly materialized. This study aims to explore the spiritual effect on students' empathy during the Covid-19 pandemic. It observes if spirituality predicts empathy and the other way around. 1004 university students from 65 universities in East Java, Indonesia, were recruited to give responses from a set of questionnaires. Smart-PLS application was used to analyze the statistical data. Findings uncovered that this measurement model is valid and reliable for spirituality (Spiritual Assessment Scale=SAS) and empathy (Interpersonal Reactivity Index=IRI) construct. Through a structural model, our study also found that spirituality and empathy have a significant reciprocal relationship (with a path coefficient of 0.564). Spirituality predicts empathy and the other way around. Our findings suggest that universities' counseling units apply spiritual strategies in counseling activities to accelerate students' empathy during the Covid-19 pandemic and to anticipate the future crisis.